Correction for age of anticardiolipin antibodies cut‐off points - Rapizzi, Elena (J Clin Lab Anal, 2000)
Immunoglobulin (Ig) isotypes G, M, and A of anticardiolipin antibodies (aCL) are considered markers of antiphospholipid syndrome (APS). They were determined by ELISA in sera of 100 healthy children aged between 6 months and 16 yrs (mean 5.4 yrs ± 3.4 SD) and 100 healthy elderly subjects aged between 65 and 103 yrs (mean 84.2 yrs ± 8.1 SD). The frequency with which they were detected was compared to that in sera of 100 healthy adults aged between 21 and 47 yrs (mean 25.8 yrs ± 5.2 SD) in order to evaluate if adult aCL cut‐off levels were fit for pediatric and elderly populations. The cut‐off points were calculated adding 2.5 SD to the mean values and, in the adult group, the results were 11.6 GPL, 7.5 MPL, and 23.9 APL for IgG, IgM, and IgA, respectively. In the children, IgG aCL were positive in 26 cases (26%), IgM and IgA aCL in 1 case (1%) respectively. Statistical comparison of these results to those of adults showed a higher significant frequency for children IgG aCL (P = 0.0001) with the major contribution by children aged between 6 months and 5 yrs, and a lower significant frequency for children IgA aCL (P = 0.041). In elderly subjects IgG aCL were positive in 12 cases (12%), IgM aCL in 4 (4%), and IgA aCL in 37 (37%). In a comparison of these values to those of adults, only elderly IgA aCL frequency was significantly higher (P = 0.0001) with the major contribution by the oldest subgroup. In order to avoid false positive results for IgG aCL in children and for IgA aCL in elderly, as well as false negative results for IgA aCL in children, we introduced three new cut‐off points: (1) 27.7 GPL for IgG aCL in children; (2) 13.8 APL for IgA aCL in children; and (3) 51.1 APL for IgA aCL in elderly subjects. These data suggest that a correction for age of aCL cut‐off levels should be considered to raise specificity and sensitivity for APS in pediatric as well as in elderly populations. J. Clin. Lab. Anal. 14:87–90, 2000. © 2000 Wiley‐Liss, Inc.